2008
DOI: 10.1002/tal.468
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear seismic response of Milad Tower using finite element model

Abstract: Milad Tower is a 436-m-tall telecommunications tower ranked as the fourth tallest structure of its kind in the world. The study of its seismic behaviour is of great importance as it is located in a highly seismic-prone region. Because of the existence of the world's largest revolving restaurant in the head structure, and also because of the highly sensitive communication devices such as TV and telecommunications antennas installed on the tower, nonlinear deformation under future earthquakes should be studied. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 4 publications
0
13
0
Order By: Relevance
“…The octagons are post tensioned in order to increase the bending capacity and stiffness of the structure to reduce the deflections. The foundation and lobby area consists of a circular foundation which is a transition structure (Yahyai et al 2009). The circular mat foundation is approximately 66 metres in diameter and sits directly beneath the transition structure.…”
Section: Introductionmentioning
confidence: 99%
“…The octagons are post tensioned in order to increase the bending capacity and stiffness of the structure to reduce the deflections. The foundation and lobby area consists of a circular foundation which is a transition structure (Yahyai et al 2009). The circular mat foundation is approximately 66 metres in diameter and sits directly beneath the transition structure.…”
Section: Introductionmentioning
confidence: 99%
“…Yahyai et al . () used finite element model analysis to study the nonlinear seismic response of Milad Tower. The results of the analysis showed that all parts of the tower behave in the plastic zone except the elements of the head structure.…”
Section: Introductionmentioning
confidence: 99%
“…Krawinkler (2006) believes that earthquake engineering is relying more and more on nonlinear analysis as a tool for evaluating structural performance and nonlinear analysis will be a good trend. Yahyai et al (2009) used finite element model analysis to study the nonlinear seismic response of Milad Tower. The results of the analysis showed that all parts of the tower behave in the plastic zone except the elements of the head structure.…”
Section: Introductionmentioning
confidence: 99%
“…However, when time and cost are considered, an alternative way is to perform nonlinear analysis using finite element method to get insights about the performance of complex buildings. Yahyai et al () used finite element model analysis to study the nonlinear seismic response of Milad Tower. Epackachi et al () conducted a seismic evaluation of a 56‐story residential reinforced concrete building based on nonlinear dynamic time history analysis of finite element model.…”
Section: Introductionmentioning
confidence: 99%